In Wicklow and West Kerry - Synge, John M. (Saga Egmont, 2022)
A beautiful collection of travel stories from some of his favourite places, ‘In Wicklow and West Kerry’ (1912) is a personal and memorable account of J.M. Synge’s journeys around Ireland. Throughout this wonderful book, Synge’s love for the Irish people and geography shines through as he regales the reader with delightful vignettes. Fans of modern travel writers like Robert Macfarlane and Bill Bryson will absolutely adore Synge\'s ‘In Wicklow and West Kerry’. Edmund John Millington Synge (1871 – 1909) was an Irish poet, playwright, and defining figure of the Irish Literary Revival. Born in County Dublin to upper-middle-class Protestants, Synge suffered from Hodgkin’s disease which led to his home-schooling. Soon after graduating from Trinity College Dublin, Synge became a renowned poet and playwright, but his success was short-lived as he passed away from cancer at 37. He is best remembered for his play ‘The Playboy of the Western World’, an incredibly controversial work at the time of its publication and performance. Regarded by Yeats as ‘the greatest dramatic genius of Ireland’, Synge has held a lasting legacy, being a key influence for acclaimed Irish playwright Samuel Beckett and the subject of Joseph O’Connor’s novel ‘Ghost Light’ (2010).